Peran Pendidikan Islam Dalam Pembentukan Karakter Siswa - M. Thoyyib (Al Hikmah: Jurnal Studi Keislaman, 2023)
Islamic education is an effort to prepare students to believe in, understand, appreciate and practice the religion of Islam through guidance, teaching and/or training activities by paying attention to the demands of respecting other religions in harmonious relations between religious communities in society to realize national unity. Character education is a concept that is instilled into a person and can shape a person to be more polite, civilized, and physically and spiritually healthy, so that they will have a better character in life. The more advanced a society is, the more important education will be for the growth and development of children. The focus of this research is on the role of Islamic education in shaping the character of students as the successors of the Indonesian nation. This research is a qualitative descriptive research. This type of research includes field research which is expected to provide an overview of the research location. Data collection techniques used include observation, interviews and documentation . The data sources for this research are the results of previous research and the results of observations as well as several interviews conducted with school principals and students. From the results of this research, it is concluded that the application of Islamic education in shaping students' character plays a very important role considering that nowadays there is a lot of moral decline among teenagers, therefore education related to the Islamic religion is needed, where Islamic religious education will raise awareness and understand students. students how to form a good character or personality. Apart from that, it can also be done by carrying out various activities such as congregational prayers, yasinan, clean Friday, congregational sunnah prayers, charity activities, practical exams, and applying the 4 S (smile, greeting, greeting and polite) and carrying out the birthday. Prophet Muhammad SAW. Keywords: Islamic education, student character